Regulation of the limb shape during the development of the Chinese softshell turtles. Issue 6 (9th September 2020) - Cordeiro, Ingrid R.; Yu, Reiko; Tanaka, Mikiko
Abstract: Interdigital cell death is an important mechanism employed by amniotes to shape their limbs; inhibiting this process leads to the formation of webbed fingers, as seen in bats and ducks. The Chinese softshell turtle Pelodiscus sinensis (Reptilia: Testudines: Trionychidae) has a distinctive limb morphology: the anterior side of the limbs has partially webbed fingers with claw‐like protrusions, while the posterior fingers are completely enclosed in webbings. Here, P. sinensis embryos were investigated to gain insights on the evolution of limb‐shaping mechanisms in amniotes. We found cell death and cell senescence in their interdigital webbings. Spatial or temporal modulation of these processes were correlated with the appearance of indentations in the webbings, but not a complete regression of this tissue. No differences in interdigital cell proliferation were found. In subsequent stages, differential growth of the finger cartilages led to a major difference in limb shape. While no asymmetry in bone morphogenetic protein signaling was evident during interdigital cell death stages, some components of this pathway were expressed exclusively in the clawed digit tips, which also had earlier ossification. In addition, a delay and/or truncation in the chondrogenesis of the posterior digits was found in comparison with the anterior digits of P. sinensis, and also when compared with the previously published pattern of digit skeletogenesis of turtles without posterior webbings. In conclusion, modulation of cell death, as well as a heterochrony in digit chondrogenesis, may contribute to the formation of the unique limbs of the Chinese softshell turtles. Abstract : We show that multiple mechanisms regulate the unique limb shape of three‐clawed Chinese softshell turtle (Pelodiscus sinensis). Cell death and senescence appear to play a minor role in reducing the partial webbings in the anterior side. Delayed chondrogenesis/ossification and truncated tips are found in posterior digits. High expression of Bmps and Msx1 in the anterior clawed digits tips is correlated with faster ossification. Highlights: Cell death and senescence shape the interdigital webbings of Pelodiscus sinensis . Delayed chondrogenesis/ossification and truncated tips are found in posterior digits, as well as differential expression of bone morphogenetic proteins and Msh homeobox 1 transcription factors.